P 4 Bioluminescence imaging visualizes osteopontin-induced neurogenesis and neuroblasts migration in the mouse brain after stroke. Issue 10 (October 2017) - Rogall, R.; Pikhovych, A.; Bach, A.; Hoehn, M.; Couillard-Despres, S.; Fink, G.R.; Schroeter, M.; Rueger, M.A.
Abstract : Background: The phosphoglycoprotein osteopontin (OPN) is upregulated in the brain following cerebral ischemia, where is exerts neuroprotective properties. We previously demonstrated OPN to increase survival and proliferation of neural stem cells (NSC) in vitro and in vivo. In culture, OPN additionally promotes NSC migration as well as a neuronal differentiation fate. Based on these data, we hypothesized OPN to induce NSC migration as well as neurogenesis in vivo as well. We here aimed to establish and visualize these effects using non-invasive in vivo imaging. Methods: Transgenic mice expressing luciferase (luc) under the doublecortin (DCX) promoter were used for brain-specific bioluminescence imaging (BLI) of DCX + neuroblasts. Focal cerebral ischemia was induced via photothrombosis (PT) in n = 27 mice, while n = 16 mice served as healthy control (CNT). Mice were randomized to receive either OPN ( n = 14 PT, n = 8 CNT), or saline ( n = 13 PT, n = 8 CNT) via a single injection into the lateral ventricle of the brain. Magnetic resonance imaging (MRI) was performed to verify and localize infarcts. BLI data was repetitively obtained for a period of 28 days in each individual animal. Ex vivo, immunohistochemistry for DCX + neuroblasts served to validate imaging data at high resolution. Results: In both healthy as well as stroke mice treated with OPN intracerebroventricularly, we observed enhanced migration of DCX + neuroblasts towards the site of OPN injection over a period of 28 days, as assessed by BLI ( p < 0.01 each). Moreover, the total flux of photons was increased in healthy mice 2 days after OPN injection, consistent with an expansion of neuroblasts numbers ( p < 0.01 ). Under ischemic conditions, OPN increased neuroblast numbers as surrogate for neurogenesis throughout the observation period of 28 days, as assessed by BLI ( p < 0.05 ). Conclusions: Data suggest positive effects of OPN on both the migration of neuroblasts as well as on neurogenesis in vivo. BLI visualizes and quantifies these effects non-invasively in the experimental animal in a longitudinal fashion, allowing to monitor the temporo-spatial dynamics of NSC mobilization under physiological conditions as well as in cerebral ischemia. The results confirm OPN as a promising drug to promote regeneration after stroke via its effects on neural stem cells.